Pedestrian-based Tsunami Evacuation Tactics for Vulnerable People using Community Assistance - Nobuhito Ohtsu (Current Advances in Geography, Environment and Earth Sciences Vol. 3, 2022)
The aim of this study was to use community evacuation tactics to create a tsunami evacuation plan and perform and evaluate the effectiveness of a drill, thus providing materials for the future selection of suitable response tactics. For community-disaster prevention based on evacuation drills and actual disaster routes, this article considers tsunami evacuation tactics for vulnerable individuals receiving assistance from response and support teams. Sixteen cases of evacuation behaviors were assessed herein through actual disasters and drills; these were organized into three formations: (A) the “independent formation,” comprising five cases in which the vulnerable person receives evacuation support from family; (B) the “pick-up formation,” comprising seven cases in which support is provided by people not living in the same residence as the vulnerable person or from multiple supporters who pick up the vulnerable person and bring him/her to the evacuation point—including cases when the vulnerable person traveled to the evacuation point via a material storage location; and (C) the “converge and dispatch formation,” comprising four cases wherein each residential block contained both residences and workplaces of the supporters and vulnerable persons, and the people first gathered at a road, park, community center, or equipment store and subsequently evacuated. This study assesses the advantages and disadvantages of the A, B, and C formations together with the positional relationships between the vulnerable persons and the supporters. Furthermore, the potential risk to both the supporters and vulnerable persons was reduced herein via mapping and the development of an appropriate evacuation plan.